Fungsi Pengawasan Lurah Kelurahan Kebonjati Kecamatan Cikole dalam Pencapaian Target Pembayaran Pajak Bumi dan Bangunan Kota Sukabumi - winda Sulastri (LPPM AMIK Citra Buana Indonesia, 2018)
The purpose of this study to determine and describe how the monitoring headman in achieving the target of tax payments on land and buildings in the village office Kebonjati Cikole districts of Sukabumi. This type of research is qualitativedescriptive research is research that aims to describe the situation in the field with the data obtained from the research.Source data used are primary data and secondary data relating to the circumstances. Data collection techniques such as library research, field research such as observation, interviews, documentation and analysis of the data over the Int ernet while authors use data on an interactive model developed by milles and Huberman. From the research results can be in theknow that the supervision headman in the achievement of the payment of taxes on land and buildings in the village office Kebonjati districts Cikole Sukabumi is pretty good, but still there are obstacles or barriers in its implementation, is stillneed for improvement and enhancement of supervision conducted by the headman of the staff employees to the target property tax.